The Effect of Labor Productivity, Exchange Rate and Inflation in Agricultural Sector on the Poverty Rate in the Island of Sulawesi Moderated by the Human Development Index - Abdul Fajar Haras1; Syarwani Canon; Asda Rauf (Cita konsultindo, 2024)
Poverty has always been a crucial issue where the discussion on it will never end. The percentage of poor people is higher in rural areas than in urban areas. The agricultural sector and poverty have a close relationship. Sulawesi Island has qualified agricultural resources. Therefore, this study aims to look at the agricultural sector which is broken down into agricultural labor productivity, farmer exchange rate, and inflation. And added HDI as moderation to the poverty rate. This research uses panel data regression analysis. The results showed that agricultural labor productivity, farmer exchange rate had a positive and significant effect on the poverty rate while inflation and human development index had a negative and significant effect. The interaction between HDI and labor productivity has a negative and significant effect, HDI and inflation show positive and significant results. Meanwhile, the interaction between HDI and farmer exchange rate has no effect.